EFSA Scientific Colloquium 24 – 'omics in risk assessment: state of the art and next steps. Issue 11 (27th November 2018) - ,; Aguilera, Jaime; Aguilera‐Gomez, Margarita; Barrucci, Federica; Cocconcelli, Pier Sandro; Davies, Howard; Denslow, Nancy; Lou Dorne, Jean; Grohmann, Lutz; Herman, Lieve; Hogstrand, Christer; Kass, George E. N.; et al.
Abstract : In recent years, the development of innovative tools in genomics, transcriptomics, proteomics and metabolomics (designated collectively as 'omics technologies) has opened up new possibilities for applications in scientific research and led to the availability of vast amounts of analytical data. The interpretation and integration of 'omics data can provide valuable information on the functional status of an organism and on the effect of external factors such as stressors. The European Food Safety Authority's (EFSA) 24th Scientific Colloquium on 'omics in risk assessment: state of the art and next steps explored the opportunities for integration of datasets produced via specific 'omics tools within the remit of EFSA's risk assessment approaches and tried to build further towards concrete paths of implementation. Discussions focused on genomics in microbial strain characterisation, metabolomics for the comparative assessment of GM plants and the use of 'omics for toxicological and environmental risk assessment. From the Colloquium it became clear that 'omics technologies are a valuable addition in some aspects of risk assessment of food and feed products and the environment, especially now that this technology is almost mature and stable. However, a consistent reporting framework for data collection, processing, interpretation, storage and curation should be further drawn up together with national and international organisations before 'omics technologies can be routinely used in risk assessment. For 'omics datasets in chemical and environmental risk assessments, the use of 'omics technologies alongside current toxicological or environmental risk assessment approaches is needed to re‐inforce confidence and expertise before implementation of these datasets as a standalone tool in risk assessment. Test cases could be worked out to enhance confidence in the use of 'omics datasets in risk assessment.